Effects of strapping application on agility performance among rugby players - Aliff, Ahmad Danish; Adnan, Aizzat; Linoby, Adam; Sazali, Razif; Zulqarnain, Muhammad; Md Yusof, Yusandra; Abidin, Muhammad Amrun Haziq (Universiti Teknologi MARA, Negeri Sembilan, 2025)
This study evaluates the impact of ankle strapping on agility performance among sixteen amateur male rugby players (ages 13 to 15) from the Victoria Institution Rugby Club. Using a randomized, counterbalanced design, participants performed the T-Test agility protocol with and without rigid athletic tape applied via the closed basketweave technique. By measuring performance times via stopwatch, the research seeks to determine whether the mechanical stability provided by strapping inadvertently hinders functional agility, ultimately informing injury prevention and training protocols in rugby.